EUROSCEPTICISM OF YOUNG PEOPLE IN CROATIA - Mišela Amanović; Martina Solenički (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The 2009 financial crisis, which resulted in the economic divergence of euro area member states, spurred a rise in Euroscepticism across the European Union. With the expected entry of Croatia into the euro area, the issue of costs and benefits of European integration has become relevant again. The main goal of the paper is to investigate the Euroscepticism of young people in Croatia. The research is conducted on a sample of 405 young people. The analysis is performed using logistic regression. The dependent variable in the model is a binomial variable that describes the respondents' answer to the question of whether or not they support the euro as the official currency in Croatia. The results of the research indicate that significant determinants of youth Euroscepticism are the exclusive national identity and economic expectations. On the one hand, Croatia's accession to the euro area is in a certain collision with a sense of commitment to one's own state in the context of exclusive national identity. In other words, young people who do not see European identity as part of their own identity will be inclined to Euroscepticism. Another important determinant of young people's Euroscepticism is economic expectations, ie their assessment of the advantages and disadvantages of joining the euro area. In other words, young people form an opinion about the euro on the individual and social-economic costs of the euro as the official currency, so those who expect more harm than good will be more prone to Euroscepticism. The results of the research contribute to a better understanding of the determinants of Euroscepticism among young people in Croatia and can be an incentive to further open the media and social space for articulating arguments about the benefits and costs of Croatia's future membership in the Economic and Monetary Union.